The Labour Party and the Nursing Profession - MacDonald, James Ramsay, 1866-1937 (London : The Labour Party (London : Co-operative Print. Society Ltd.), 1927)
1927 1927 1920s 40 pages 16 A number of fever hospitals have adopted the Superannuation Act for Local Government officers, a scheme under which the nurses contribute 3 3/4 per cent. of salary and emoluments and are obliged to retire at 60. The fever hospitals under the Metropolitan Asylums Board come under the Poor Law Officers' Superannuation Act. Sixty-nine of the hospitals in London are now starting a general contributory system of pensions for nurses organised by the King's Hospital Fund. The Provisional Council anticipate that the scheme will be in actual operation by January 1st, 1927, or possibly earlier. The scheme is to be on the lines of the Federated Superannuation System for Universities whereby insurance policies are taken out for individual employes. The total contribution is to be 15 per cent. of salary and emoluments, 10 per cent. being paid by the hospital and 5 per cent. by the nurses. The scheme is to include all female professional nurses, whether nursing the sick or doing work under a public authority. It is to be compulsory for all new entrants into the service of the hospital to join the scheme or to continue membership, if already members. It also includes all probationers after one year's training, but it will be open to each hospital to decide whether to admit probationers after one year's training or not until they are registered as nurses. The nurses will have a choice of alternative benefits including (a) endowment assurance policies with profits; (b) deferred annuity policies with return of premiums; (c) deferred annuity policies without return of premiums. Policies are to mature at 55. A nurse migrating within the nursing service is to take the benefit of both contributions. If she leaves the profession within five years of joining the scheme she is to take the benefit of her own contributions only; if, after five years, she takes the benefit of both contributions. No immediate special provision for disablement is made other than the surrender value of the policies, but the question is to be considered by the Council of the scheme. The Provisional Executive Committee consists of ten representatives of participating hospitals, one representative nominated by the Incorporated Association of Hospital Officers, and one representative nominated by the College of Nursing. MENTAL HOSPITALS. Nurses in mental hospitals are strongly organised, belonging largely to the National Asylum Workers' Union, an organisation with 11,000 members, all of whom, however, are not nurses. The union and the Mental Hospitals Association have an agreement covering working conditions. As a result of this agreement, the working week for members of the indoor staff does not exceed 66 hours, inclusive of meal time. Not less than six and a-quarter hours are allowed for meals, bringing the maximum hours worked to 59¾. The average number of hours worked per week on both day and night duty is 56. Each member is given three weeks' holiday per year. Contrary to the practice in other hospitals, nurses pay for their board, lodging, and laundry. Wages are paid weekly unless other arrangements are desired by the majority of the staff. A lower scale of wages is paid to nurses working in institutions situated in rural areas than to nurses working in institutions situated in urban areas; and a lower scale is paid to female nurses than to male nurses. The method of rising from the minimum differs as between nurses appointed before or after June, 1922, in view of the examinations then instituted by the Medico-Psychological Association for Proficiency in Mental Nursing. The 126/TG/RES/X/1036A/14